Commercial extract of coffee (Coffea arabica L.) and mango essence as potential attractants for Ceratitis capitata (Wiedemann) (Diptera: Tephritidae) - Araújo, Alexandre Santos; Leal , Leandro do Santos; Correia, Lorena Araújo Peixoto; Andrade, Jennifer da Silva; Barreto, Artur Magno Fiais; Costa, Carina Cristina de Oliveira Santos; Cardoso, Amanda Amorim Silva; Galvão-Silva, Fábio Luís; Passos-Roriz, Alzira Kelly; Mesquita, Paulo Roberto Ribeiro de; Joachim-Bravo, Iara Sordi (EntomoBrasilis, 2022)
Various host compounds have been investigated to produce an alternative attractant for monitoring and controlling pest insects. Several studies evidenced that volatile molecules released by coffee and mangoes attracted both male and female Ceratitis capitata (Wiedemann), a significant pest in fruit crops. In this study, we tested the effectiveness of the commercial glycolic extract of coffee (Coffea arabica L.) and a commercial mango essence (Mangifera indica L.) to attract C. capitata. We identified the main volatile compounds (VOCs) emitted from such products. The experiments were conducted in field cages and showed that the glycolic extract of coffee attracts both sexes of C. capitata, while the mango essence attracts only males. After seven days, the pH of the coffee extract and mango essence did not change. These results indicate that attractants based on commercial fruit extracts and essences can be an option for integrated pest management of the Mediterranean fruit fly in orchards.